If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -5y)(x + 3y) = 0 Multiply (X + -5y) * (x + 3y) (X(x + 3y) + -5y * (x + 3y)) = 0 ((x * X + 3y * X) + -5y * (x + 3y)) = 0 ((xX + 3yX) + -5y * (x + 3y)) = 0 (xX + 3yX + (x * -5y + 3y * -5y)) = 0 (xX + 3yX + (-5xy + -15y2)) = 0 Reorder the terms: (xX + -5xy + 3yX + -15y2) = 0 (xX + -5xy + 3yX + -15y2) = 0 Solving xX + -5xy + 3yX + -15y2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3yX' to each side of the equation. xX + -5xy + 3yX + -3yX + -15y2 = 0 + -3yX Combine like terms: 3yX + -3yX = 0 xX + -5xy + 0 + -15y2 = 0 + -3yX xX + -5xy + -15y2 = 0 + -3yX Remove the zero: xX + -5xy + -15y2 = -3yX Add '15y2' to each side of the equation. xX + -5xy + -15y2 + 15y2 = -3yX + 15y2 Combine like terms: -15y2 + 15y2 = 0 xX + -5xy + 0 = -3yX + 15y2 xX + -5xy = -3yX + 15y2 Reorder the terms: xX + -5xy + 3yX + -15y2 = -3yX + 3yX + 15y2 + -15y2 Combine like terms: -3yX + 3yX = 0 xX + -5xy + 3yX + -15y2 = 0 + 15y2 + -15y2 xX + -5xy + 3yX + -15y2 = 15y2 + -15y2 Combine like terms: 15y2 + -15y2 = 0 xX + -5xy + 3yX + -15y2 = 0 The solution to this equation could not be determined.
| y=x^3-81x | | 3x^2-15-2x=0 | | 72=3(3z) | | 9(g-5h)= | | 10x-9y=2 | | 15x+7x-2=0 | | x+x+74=180 | | f(x)=3x^2+5x-7 | | 30=22.5/r | | (7x+3)(2x+6)=0 | | y=-x^2-10x+25 | | 10(b+4c)= | | 3x+34=9x-2 | | 1/(2sin(2x) | | 89-73=27y-31y | | 2x-(-4)=212 | | 2a+7=51 | | 2v-2=3v+15 | | 0.4n-1=35 | | 5x^2-7=49 | | 4b+36=9b+66 | | 4p-6=2p+4 | | (2x+4)+(3x^2-5x-3)=0 | | 0=-12p | | .5x^2-2x+3=0 | | -(4y+1)-(3y-8)=-1 | | 3x^2+11+5=0 | | 12=7/10g=44 | | 10(x+4)-2x=4x+2(2x+10)+20 | | 4e^3x=20 | | 4x^2+4x-17=0 | | 11(8r+3)2(9-6r)= |